2017
DOI: 10.4103/atm.atm_364_16
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary consequences of hypothyroidism

Abstract: BACKGROUND:Although hypothyroidism has an insidious onset and relatively asymptomatic, exertional dyspnea and fatigue can be the presenting complaints.OBJECTIVES:The aim is to assess functional lung impairment in hypothyroid patients both at rest and during exercise.METHODS:A case-control study was carried out on 42 patients with newly diagnosed hypothyroidism and 12 control subjects. Hypothyroidism was diagnosed based on high value of thyroid stimulating hormone (TSH) ≥6 μIU/ml, and low value of free thyroxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…In addition to impairing normal metabolic processes, hypothyroidism is a multifaceted condition associated with increasing digestive system, pulmonary, and hematologic complications. [8][9][10][11][12] Hypothyroidism has a significant impact on the digestive system, affecting function in the esophagus down to the colon. The findings in our study are consistent with that of Ling et al who found that 2.8% of patients with hypothyroidism experienced gastrointestinal complications within the first 30 days following THA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to impairing normal metabolic processes, hypothyroidism is a multifaceted condition associated with increasing digestive system, pulmonary, and hematologic complications. [8][9][10][11][12] Hypothyroidism has a significant impact on the digestive system, affecting function in the esophagus down to the colon. The findings in our study are consistent with that of Ling et al who found that 2.8% of patients with hypothyroidism experienced gastrointestinal complications within the first 30 days following THA.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit both hypothyroidism 82 , and hyperthyroidism 83 may be associated with exertional dyspnoea, and fatigue can be the presenting complaint, their relationship with COPD has not been investigated.…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…I have read with interest the case–control study by Sadek et al on the pulmonary consequences of hypothyroidism in a cohort of Egyptian patients. [ 1 ] In the methodology, the authors employed spirometry to measure various components of pulmonary function tests (PFTs), namely, forced vital capacity (FVC), FVC%, forced expiratory volume in 1 s (FEV1s), FEV1s%, FEV1s/FVC, and forced expiratory flow (FEF 25–75 )%. [ 1 ] The authors found that FVC% and FEF 25–75 % were significantly reduced in the hypothyroid group ( P = 0.014, P = 0.000, respectively)compared to the control group.…”
mentioning
confidence: 99%
“…[ 1 ] In the methodology, the authors employed spirometry to measure various components of pulmonary function tests (PFTs), namely, forced vital capacity (FVC), FVC%, forced expiratory volume in 1 s (FEV1s), FEV1s%, FEV1s/FVC, and forced expiratory flow (FEF 25–75 )%. [ 1 ] The authors found that FVC% and FEF 25–75 % were significantly reduced in the hypothyroid group ( P = 0.014, P = 0.000, respectively)compared to the control group. [ 1 ] I presume that these findings ought to be cautiously interpreted.…”
mentioning
confidence: 99%
See 1 more Smart Citation